Synthesis of lithium manganese oxide/graphene nanoplatelets nanocomposite for aqueous supercapattery - Low, Jo Ring (2022)
The low energy density of supercapacitor and low power density of lithium-ion batteries limits its real-life application. Supercapattery is an innovative hybrid energy storage device, which combines the merits of rechargeable batteries and supercapacitors into a single device. Spinel-structured lithium-manganese oxide (LMO) cathode material is one of the intriguing energy storage material due to its low cost and low toxicity. Besides, it has been successful commercialized for large scale energy storage, but its low conductivity and stability resulting in fast capacity fading. Composites of LMO nanoparticles in a graphene matrix can be used to compensate their low conductivity. In addition, synthesis methodology of LMO plays an important duty to improve the power and energy density of a supercapattery as it affects the electrochemical properties of the LMO cathode. Herein, lithium manganese oxide/graphene nanoplatelets (LMO/GNPs) composite was synthesized by both hydrothermal (HT) and solid-state reaction (SSR) methods to investigate the effect of preparation methods on the physicochemical properties and electrochemical behavior of the composite as the cathode for supercapattery applications. This cathode is characterized by different physicochemical techniques to analyze the structure of crystalline materials, surface area, and morphology of the composites such as FE-SEM, N2 absorption and desorption, XRD, and Raman spectroscopy. Meanwhile, the electrochemical performance of the fabricated cathode is evaluated within a Swagelok cell with GNPs as an anode, in an eco-friendly and safer aqueous electrolyte of 1 M Li2SO4. Nylon membranes were soaked in the aqueous electrolyte to act as the separator to separate the anode and cathode physically and facilitate the lithium-ion transportation in the cell. LMO/GNPs prepared via the HT approach are found to provide a well-distribution of nanometer-size particles and enhance the specific surface area, which led to an improvement in electrochemical properties compared to the SSR method. The assembled supercapattery of h-LMO has achieved the specific capacity and capacitance of 26.2 mA h g-1 and 191.98 F g-1. Interestingly, the incorporation of 1 mg GNPs on the surface of LMO by the HT method led to a 70% increase in specific capacitance and initial discharge capacity. H-LMO/GNPs1 exhibits a high energy density and power density of 39.07 W h kg-1 at 925.40 W kg-1, respectively. This is due to the high conductive properties of GNPs that promote faster electron transfer kinetics for efficient Li+ diffusion. Improved cycle stability of 82% capacity retention for over 1000 consecutive cycles is obtained for h-LMO/GNPs1 based cathode. Ultimately, the method of preparing LMO/GNPs composites showed great influence on the surface chemistry, surface area, and the resulting supercapattery performance.